Calling on dragons - Wrede, Patricia C., 1953- (Wrede, Patricia C., 1953- Enchanted Forest chronicles, 2003)
Queen Cimorene turns to her friends Morwen, Telemain, and Kazul for help when troublesome wizards make their way back into the Enchanted Forest and begin to soak up its magic.